MOLA HIDATIFORME: UM RELATO DE CASO - Felipe José Amaral de Castro¹; Gustavo Rodrigues Baldoino; João Batista Gomes; Leôncio de Faria Gonçalves; Letícia Noronha Gonzaga; Wanessa Nunes Pinto Jubé (UniEVANGÉLICA, 2016)
Objectives: We relate a case of gestational throphoblastic neoplasia (GTN) of the complete hydatiform mole variant occurred in the city of Anápolis-GO and also revised the literature about the subject. Case report: In first gynecological consultaltion pacient shows high levels of beta-HCG, uterine height imcompatible with gestational age and inaudible fetal heart beat. The ultrasound confirms gestational trophoblastic neoplasia being done the first curettage as soon as possible. With a month being passed are realized two more curetagges and the patient is forwarded to the Santa Casa of Anápolis, where after further examination were found beta-HCG of 142000 mUI/ml and hemoglobin of 10,3 g/dl. Her fourth curettage is realized and she is indicated to follow therapy in the Cancer Hospital of Anápolis. However, before that, she returns to the Santa Casa with pelvic aching, living and bright red vaginal bleeding, with no odor associated, following, therefore, with new betaHCG dosage (52475,46 mUI/mL) e with new curettage being done. Currently, patient continues in chemotherapy and has progressively decreasing beta-HCG levels. Final considerations:We emphasize with this story description the necessity of appreciation of pre-natal routines aiming the correct and premature diagnosis of the variety of NTG cases, as also the adequate following in the expectation of preventing relapses.